A survey of the genus Sorolopha Lower, 1901 in the northern part of Vietnam (Lepidoptera: Tortricidae, Olethreutinae) - Le, Xuanvi; Qi, Mu Jie; Park, Kyu-Tek; Bae, Yang-Seop (Zootaxa, 2013)
A survey of the genus Sorolopha Lower, 1901 in the northern part of Vietnam revealed the presence of 10 species, includ-ing S. cucphuongensis Bae & Le, sp. nov. Most of the species previously were reported by various authors, but S. rube-scens Diakonoff, 1973 and S. cyclotoma Lower, 1901 are newly recorded for the country. All species are diagnosed, and figures of the adults and genitalia are provided, along with a key to species of Sorolopha in Vietnam.